Tbx5 navigates through the labyrinth of adult cardiac regeneration. (14th October 2021) - Siatra, P; Hatzianastasiou, N; Vatsellas, G; Manolakou, T; Papapetropoulos, A; Balafas, E; Ruchaya, P J; Kostomitsopoulos, N G; Mouchtouri, E; Mavroidis, M; Thanos, D; Yashiro, K; et al.
Abstract: Background: Heart failure is the major cause of death and morbidity in industrialized countries with an estimated 23 million people affected per year, representing 30% of all global deaths. Injury to the adult mammalian cardiac muscle, often leads to a heart attack due to irreversible loss of a large number of cardiomyocytes (CM) and other cardiac interstitial cells, creating an unmet need for identifying a cardiac progenitor cell (CPC) population for cardiac replenishment. In contrast, amphibians and neonatal rodents possess the ability to regenerate their heart upon injury. It has been suggested recently that idle cardiac regenerative mechanisms may be present in adult mammals, inhibited by exogenous cues, or lack of. Murine and human CPCs can be isolated through the expression of Pdgfra, Kdr, and our novel surface marker, Gfra2. In addition, the expression of the embryonic transcription factor TBX5, is paramount for differentiation towards a cardiomyocyte fate. Therefore, Tbx5-expressing CPCs could be an effective target for proof-of-concept studies in the heart repair field, inclined to pharmacological modulation in patients with ischemic heart disease. Purpose: To characterise an adult Tbx5-expressing CPC population in the injured heart. Using a developmental approach to two adult heart injury murine models, we show that Tbx5-expressing CPC exist in the injured adult mammalian heart, with a molecular signature that strongly correlates with that of embryonic and neonatal CPCs. Methods: A well-defined tamoxifen-induced Tbx5-Cre; Rosa26R-eYFP/eYFP transgenic mouse model was employed, where myocardial infarction (MI) was induced through reperfusion/ischemia or chemical injury. Cardiac cells expressing YFP+ cells were collected from the adult injured hearts five to seven days post-injury. Flow-cytometric and single-cell mRNA-seq analysis was performed in order to collect and compare those YFP+ cells to control adult uninjured cardiac interstitial cells, and early neonatal-derived CPCs. Results: Immunohistochemical analysis indicated that YFP+ interstitial cells were mostly present in the injury site, but also in distal cardiac areas. Flow cytometric analysis of live cells pinpoint these YFP+ cells are part of a CPC-like population. Single-cell mRNA transcriptomic analysis revealed that YFP+ cells resemble early postnatal CPC. Yet, YFP+ cells never expressed CM markers in vivo, but they did differentiate into CM-like cells, in vitro. Conclusions: Upon MI, the adult heart possess an interstitial cell population that transiently re-activates the pioneer cardiac embryonic transcription factor Tbx5. The Tbx5-expressing cell population transcriptomically resembles that of CPC, which could promote CM regeneration upon neonatal injury. We show that Tbx5 lies in the centre of a novel adult CPC population. The adult heart microenvironment may hinder mammalian CM regeneration through regulation of the Tbx5-induced cardiac gene program. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Hellenic Foundation for Research & Innovation